Cell-in-the-loop pattern formation with optogenetically emulated cell-to-cell signaling - Melinda Liu Perkins (Nature Portfolio, 2020)
Synthetic biological pattern formation is challenging to engineer due to theoretical complexity and practical limitations. Here, the authors introduce a cell-in-the-loop approach in which cells interact through in silico signaling.